2021
DOI: 10.1016/j.heliyon.2021.e06480
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning approaches for the prediction of soil aggregate stability

Abstract: Currently, many Pedotransfer Functions (PTFs) are being developed to predict certain soil properties worldwide, especially for difficult and time-consuming parameters to measure. However, very few studies have been done to assess the feasibility of using PTFs (regression or machine learning methods) for predicting soil aggregate stability. Also, the Random Forest (RF) method has never been used before to predict this parameter, and no study was found concerning the use of PTFs methods to estimate soil paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Many previous studies can also support these results (Besalatpour et al, 2014;Shi et al, 2020;Jones et al, 2021;Kamamia et al, 2021). In contrast, Bouslihim et al (2021) reported a low contribution of remote sensing indices in estimating SAS, and this was justified by the presence of other parameters that often reduced the role of remote sensing indices. Although some studies have reported the role of climate in SAS distribution (Cerdà, 2000;Guan et al, 2018;Le Bissonnais et al, 2018), these data were not used in the current paper due to the small size of the study area and the limited spatial change for climatic conditions.…”
Section: Determining the Relative Importance Of Variablesmentioning
confidence: 59%
See 3 more Smart Citations
“…Many previous studies can also support these results (Besalatpour et al, 2014;Shi et al, 2020;Jones et al, 2021;Kamamia et al, 2021). In contrast, Bouslihim et al (2021) reported a low contribution of remote sensing indices in estimating SAS, and this was justified by the presence of other parameters that often reduced the role of remote sensing indices. Although some studies have reported the role of climate in SAS distribution (Cerdà, 2000;Guan et al, 2018;Le Bissonnais et al, 2018), these data were not used in the current paper due to the small size of the study area and the limited spatial change for climatic conditions.…”
Section: Determining the Relative Importance Of Variablesmentioning
confidence: 59%
“…What is interesting is the absence of very unstable soils throughout the region (MWD < 0.4 mm) with a domination of the two classes: moderately stable (0.8 < MWD < 1.3 mm) and stable (1.3 < MWD < 2.0 mm). This can be underpinned by the findings by Bouslihim (2020), Bouslihim et al (2021) regarding the low soil erosion rates in the region; moreover, the only exposed area to erosion is the downstream part of the El Himer watershed due to the factors mentioned earlier (anthropogenic factors and topography).…”
Section: Spatial Prediction Of Soil Aggregate Stabilitymentioning
confidence: 80%
See 2 more Smart Citations
“…The experimental results show that the prediction capability of SVM is better than that of the MLR and ANN models with the same number of input parameters and data points. Y Bouslihim et al 19 propose ML approaches to predict SAS. In the study, they compared the ability of RF and MLR to predict MWD as an SAS index.…”
Section: Introductionmentioning
confidence: 99%